Transport Policy Related to Road Transport and Sustainable Development - Jozef Gnap; Vladimir Konecny (Communications, 2003)
Development in almost all sectors of economy will immediately affect the transport sector. We can say that growth in economy leads automatically to growth in road transport. As a continuous process the road transport industry produces vehicles by new technologies and transport operators finance this section by purchasing new trucks and coaches. There is a continual and tightened process in the road transport legislation, the EU has elaborated conceptions for achieving sustainable development. The state transport policy of the Slovak Republic has to reflect specified results and conceptions, otherwise road transport in the Slovak Republic becomes the brake of sustainable development.